KEMAMPUAN MENULIS TEKS NEGOSIASI DENGAN MENGGUNAKAN METODE PICTURE AND PICTURE DI SMK - Nurpadilah, Siti; E, Yasri Fazriah; Kartini, Cucu (IKIP Siliwangi, 2018)
This study aims to determine (1) planning the process of learning to write text negotiation using picture and picture method; (2) implementation of learning process of writing negotiation text using picture and picture method; (3) improvement of learning outcomes after using the method of learning picture and picture and increasing interest in learning and attitude of learners in learning. The research method used is experimental research - pre-experimental designs with the selection of one-group model pretest-posttest design. The data obtained from this study is the test results consisting of pretest and posttest. Pretest results are obtained before the learners get treatment, whereas posttest is the result of treatment. The average learning result of writing negotiating text before using picture and picture method is 61,84 and after using picture and picture method increase with average 77,60 Writing student has increased. The increase of pretest with posttest result, ie 69.72. The result proves that using picture and picture method can improve students' ability to write negotiation text.